CFD simulation of flow around angle of attack and sideslip angle vanes on a BAe Jetstream 3102 - Part 1 - Bennett, Christopher J.; Lawson, Nicholas J.; Gautrey, James E.; Cooke, Alastair K. (Elsevier, 2017)
CFD modelling techniques are exploited to investigate the local velocity field around angle of attack and sideslip angle sensors fitted to the nose of a modified BAe Jetstream 3102 small airliner. Analysis of the flow angularity at the vane locations has allowed the vanes response to varying flight conditions to be predicted and errors in the readings to be quantified. Subsequently, a more accurate calibration of the system is applied to the current configuration on the Jetstream, and a better understanding of the position error with respect to the vane locations is obtained. The above aircraft was acquired by Cranfield University in 2003 with subsequent flow angle vane modifications taking place in 2005. The aircraft is currently in operation with the National Flying Laboratory Centre (NFLC) for research and demonstration purposes.